Risk Factors for Perinatal Deaths - A.A. AL-Gafoor, Intisar (Tikrit Journal of Pharmaceutical Sciences, 2023)
Perinatal mortality is significant health problem throughout the ward .it is prevalence is quite high specially in developing countries (16 ) .most of the causes are treatable and fetal out come can be improved by recognizing the site of the problem and provision good health care facilities during ante partum and intrapartum periods. To investigate the fetal and maternal factors associated with perinatal deaths. Case control study was designed to study the main risk factors for perinatal deaths at AL-batool Teaching Hospital /SBCU from1st January 2009 to 30S December 2009.505 registerated perinatal deaths were considered as cases ,a sample of 505 controls obtained among the survivals of the perinatal period. The data collected by questionnaire form to assess main causes of perinatal deaths such as respiratory distress syndrome, sepsis, birth asphyxia ,low birth weight , congenital abnormality ,gender of new born .In addition maternal risk factors like history of pregnancy induced hypertension ,history of ante partum hemorrhage, women parity ,maternal age , maternal medical disorder, more over history of infertility ,mode of deliveries, ruptured uterus. Regarding causes of perinatal deaths; respiratory deaths syndrome, sepsis, birth asphyxia, low birth weight, congenital abnormality , all of them were found to be highly significant associated with the occurrence of perinatal deaths . According to maternal variable; maternal age<35 ,parity<5 pregnancy Induced hypertension ,history of ante partum hemorrhage ,ruptured uterus, unexplained causes of deaths were all found to be among the significant risk factors associated with perinatal loss. This study showed although there is clear reduction in the PNMMR after 2003, but still no changes in the main causes and risk factors for perinatal deaths and it is same to most of studies done in different countries in Iraq and world. The overall aim is to reduce the risk of perinatal death, effectively implementing the problems identified and solutions to the problems identified by application and designating practical clinical guide line.